Activation of PPARs α, β/δ, and γ Impairs TGF-β1-Induced Collagens' Production and Modulates the TIMP-1/MMPs Balance in Three-Dimensional Cultured Chondrocytes. (11th August 2010) - Poleni, Paul-Emile; Etienne, Stephanie; Velot, Emilie; Netter, Patrick; Bianchi, Arnaud
Abstract : Background and Purpose . We investigated the potency of Peroxisome Proliferators-Activated Receptors (PPARs)α, β /δ, andγ agonists to modulate Transforming Growth Factor-β 1 (TGF-β 1-) induced collagen production or changes in Tissue Inhibitor of Matrix Metalloproteinase- (TIMP-) 1/Matrix Metalloproteinase (MMP) balance in rat chondrocytes embedded in alginate beads. Experimental Approach . Collagen production was evaluated by quantitative Sirius red staining, while TIMP-1 protein levels and global MMP (-1, -2, -3, -7, and -9) or specific MMP-13 activities were measured by ELISA and fluorigenic assays in culture media, respectively. Levels of mRNA for type II collagen, TIMP-1, and MMP-3 & 13 were quantified by real-time PCR. Key Results . TGF-β 1 increased collagen deposition and type II collagen mRNA levels, while inducing TIMP-1 mRNA and protein expression. In contrast, it decreased global MMP or specific MMP-13 activities, while decreasing MMP-3 or MMP-13 mRNA levels. PPAR agonists reduced most of the effects of TGF-β 1 on changes in collagen metabolism and TIMP-1/MMP balance in rat in a PPAR-dependent manner, excepted for Wy14643 on MMP activities. Conclusions and Implications . PPAR agonists reduce TGF-β 1-modulated ECM turnover and inhibit chondrocyte activities crucial for collagen biosynthesis, and display a different inhibitory profile depending on selectivity for PPAR isotypes.